Gli3 Regulates Vomeronasal Neurogenesis, Olfactory Ensheathing Cell Formation, and GnRH-1 Neuronal Migration - Taroc, Ed Zandro M.; Naik, Ankana S.; Lin, Jennifer M.; Peterson, Nicolas B.; Keefe, David L.; Genis, Elizabet; Fuchs, Gabriele; Balasubramanian, Ravikumar; Forni, Paolo E. (The Journal of neuroscience, 2020)
During mammalian development, gonadotropin-releasing-hormone-1 neurons (GnRH-1ns) migrate from the developing vomeronasal organ (VNO) into the brain asserting control of pubertal onset and fertility. Recent data suggest that correct development of the olfactory ensheathing cells (OEC) is imperative for normal GnRH-1 neuronal migration. However, the full ensemble of molecular pathways that regulate OEC development remains to be fully deciphered. Loss-of-function of the transcription factor Gli3 is known to disrupt olfactory development, however, if Gli3 plays a role in GnRH-1 neuronal development is unclear. By analyzing Gli3 extra-toe mutants (Gli3 Xt/Xt ), we found that Gli3 loss-of-function compromises the onset of achaete-scute family bHLH transcription factor 1 (Ascl-1) + vomeronasal progenitors and the formation of OEC in the nasal mucosa. Surprisingly, GnRH-1 neurogenesis was intact in Gli3 Xt/Xt mice but they displayed significant defects in GnRH-1 neuronal migration. In contrast, Ascl-1 null mutants showed reduced neurogenesis for both vomeronasal and GnRH-1ns but less severe defects in OEC development. These observations suggest that Gli3 is critical for OEC development in the nasal mucosa and subsequent GnRH-1 neuronal migration. However, the nonoverlapping phenotypes between Ascl-1 and Gli3 mutants indicate that Ascl-1, while crucial for GnRH-1 neurogenesis, is not required for normal OEC development. Because Kallmann syndrome (KS) is characterized by abnormal GnRH-1ns migration, we examined whole-exome sequencing data from KS subjects. We identified and validated a GLI3 loss-of-function variant in a KS individual. These findings provide new insights into GnRH-1 and OECs development and demonstrate that human GLI3 mutations contribute to KS etiology. SIGNIFICANCE STATEMENT The transcription factor Gli3 is necessary for correct development of the olfactory system. However, if Gli3 plays a role in controlling GnRH-1 neuronal development has not been addressed. We found that Gli3 loss-of-function compromises the onset of Ascl-1 + vomeronasal progenitors, formation of olfactory ensheathing cells in the nasal mucosa, and impairs GnRH-1 neuronal migration to the brain. By analyzing Ascl-1 null mutants we dissociated the neurogenic defects observed in Gli3 mutants from lack of olfactory ensheathing cells in the nasal mucosa, moreover, we discovered that Ascl-1 is necessary for GnRH-1 ontogeny. Analyzing human whole-exome sequencing data, we identified a GLI3 loss-of-function variant in a KS individual. Our data suggest that GLI3 is a candidate gene contributing to KS etiology.